2011
DOI: 10.1007/s13258-011-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and demographic history of the fat greenling Hexagrammos otakii

Abstract: Fat greenling (Hexagrammos otakii) is an important commercial fish in the Northwestern Pacific, being distributed along the coastal waters of the East/Japan Sea and the Yellow Sea. To investigate population genetic structure and demographic history of this species, one hundred and fifty five individuals were collected from five localities in the distribution range of the species and sequence variations in the mitochondrial genes COI, COIII-ND3-ND4L, and cytochrome b were examined. For all the genes in every sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Several marine fishes around Korea and Japan exhibit a similar pattern of genetic homogeneity among populations. For example, fat greenling H. otakii, a sister species of spotty belly greenling did not show any genetic differentiation among the stocks in the Yellow Sea, the Korea strait and the East Sea in the studies of cytochrome b, COI and COIII-ND3-ND4L gene regions (Habib et al 2011). Japanese sea bass Lateolabrax japonicus and blackfin flounder Glyptocephalus stelleri form a panmictic population around the Korea and the Japan coastal waters (Liu et al 2006a;Xiao et al 2010).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Several marine fishes around Korea and Japan exhibit a similar pattern of genetic homogeneity among populations. For example, fat greenling H. otakii, a sister species of spotty belly greenling did not show any genetic differentiation among the stocks in the Yellow Sea, the Korea strait and the East Sea in the studies of cytochrome b, COI and COIII-ND3-ND4L gene regions (Habib et al 2011). Japanese sea bass Lateolabrax japonicus and blackfin flounder Glyptocephalus stelleri form a panmictic population around the Korea and the Japan coastal waters (Liu et al 2006a;Xiao et al 2010).…”
Section: Discussionmentioning
confidence: 88%
“…In the case of a sudden expansion of a population, the rate of stochastic loss of haplotypes slows down and more haplotypes become retained than lost by random genetic drift (Avise et al 1984). This kind of genetic composition has been observed in a number of fish species including fat greenling (h = 0.69 -0.96, π = 0.002 -0.004) (Habib et al 2011), blackfin flounder (h = 0.99, π = 0.014) (Xiao et al 2010), redtile fish (h = 0.93, π = 0.008) (Nohara et al 2010), spotedtail gobby (h = 0.60 -0.95, π = 0.0025 -0.0064) (Song et. al.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The high level of haplotypic diversity and low π value in E. tetradactylum populations in Bay of Bengal and Australian populations suggest that this fish could have experienced a population expansion after a period of low effective population size (Grant and Bowen, 1998). This type of genetic structure has been observed in threadfin fish, E. rhadinum (Sun et al, 2013), long-tailed hake, Macruronus magellanicus (Machado-Schiaffino and Garcia-Vazquez, 2011) and fat greenling, Hexagrammos otakii (Habib et al, 2011 population expansion in most of the E. tetradactylum populations. Moreover, the haplotype network also confirmed recent population expansion following a population bottleneck in most of the studied populations.…”
Section: Tests Of Neutrality and Population Expansion Estimationmentioning
confidence: 83%
“…In addition a remarkable reduction was observed in genetic diversity of the Zhoushan population (h = 0.595 ± 0.109, π = 0.001 ± 0.001 55) compared to the Qidong (h = 0.782 ± 0.058, π = 0.00212 ± 0.0035) and Zhuhai populations (h = 0.780 ± 0.059, π = 0.00222 ± 0.00282). Genetic variation within populations can be reduced through genetic drift or bottleneck in the particular population Habib et al, 2011). An earlier study (Chang et al, 2012) reported that, overfishing and concomitant habitat loss in this Fig.…”
Section: Tests Of Neutrality and Population Expansion Estimationmentioning
confidence: 99%